2007
DOI: 10.1001/archsurg.142.9.881
|View full text |Cite
|
Sign up to set email alerts
|

Breast Abscess Bacteriologic Features in the Era of Community-Acquired Methicillin-Resistant Staphylococcus aureus Epidemics

Abstract: Increasing rates of community-acquired methicillin-resistant Staphylococcus aureus (MRSA) infections have also affected the microbial profile of breast abscesses.Objective: To update the decade-old bacteriologic description of breast abscesses to improve the choice of initial antibacterial drug therapy.Design: Retrospective case series.Setting: County hospital emergency department.Patients: Forty-four women (mean age, 41 years; age range, 20-63 years) with breast abscesses.Methods: All cultures from the breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
60
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 14 publications
7
60
1
3
Order By: Relevance
“…Among adults with an abscess and surrounding erythema, the presence of a central black eschar had a positive predictive value of 94% and a negative predictive value of 45% for an MRSA isolate (113). CA-MRSA abscesses can be found in diverse anatomical locations, including the breast (615,855,1003), vulva (898), hand after clenched-fist injury (63), and neck (353,426). However, SSTIs can vary in appearance and can also present as folliculitis, paronychia, furuncle, felon, cellulitis with drainage (628), or lymphadenitis (353).…”
Section: Patients With Sstismentioning
confidence: 99%
“…Among adults with an abscess and surrounding erythema, the presence of a central black eschar had a positive predictive value of 94% and a negative predictive value of 45% for an MRSA isolate (113). CA-MRSA abscesses can be found in diverse anatomical locations, including the breast (615,855,1003), vulva (898), hand after clenched-fist injury (63), and neck (353,426). However, SSTIs can vary in appearance and can also present as folliculitis, paronychia, furuncle, felon, cellulitis with drainage (628), or lymphadenitis (353).…”
Section: Patients With Sstismentioning
confidence: 99%
“…Staphylococcus aureus is a pathogen frequently isolated from mastitis milk or mammary abscesses in the lapine, ovine, bovine, and human species (4,5,23,41,53). The recognition of S. aureus by the mammary gland is not as well known as the recognition of Escherichia coli, another major pathogen for the mammary gland.…”
mentioning
confidence: 99%
“…Staphylococcus aureus and Staphylococcus epidermidis are the commonest pathogens isolated from breast abscesses, [5][6][7][8][9] with Proteus spp. and anaerobic bacteria (including Bacteroides spp.…”
Section: Discussionmentioning
confidence: 99%
“…Moazzez et al 5 found S. aureus in 32% of cultures, with more than half of these isolates being methicillin-resistant S. aureus (MRSA). Walker et al 6 found S. epidermidis to be the commonest isolated aerobic bacteria in their study, with 60% of cultures yielding this organism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation